Genetic Basis of Sudden Unexpected Death in Epilepsy - Bagnall, Richard D.; Crompton, Douglas E.; Semsarian, Christopher (Frontiers in Neurology, 2017)
People with epilepsy are at heightened risk of sudden death compared to the general population and the leading cause of epilepsy-related premature mortality is sudden unexpected death in epilepsy (SUDEP). Postmortem investigation of people with SUDEP, including histological and toxicological analysis, does not reveal a cause of death and the mechanisms of SUDEP remain largely unresolved. Emerging studies in humans and animal models suggest there may be an underlying genetic basis to SUDEP in some cases. Inherited cardiac arrhythmia syndromes, such as the long QT syndrome, cause unexplained sudden cardiac death, and pathogenic variants previously found in people with long QT syndrome are also found in SUDEP. Furthermore, the long QT gene, KCNH2, is among the genes with the highest number of variants in SUDEP compared to people without epilepsy. Some genetic epilepsies have an increased risk of SUDEP. For example, there is a high mortality rate in Dravet syndrome, with approximately half of deaths due to SUDEP, and pathogenic variants in the familial focal epilepsy gene, DEPDC5, are more common in SUDEP than in people without epilepsy. Observational reports of SUDEP, or near SUDEP, in epilepsy monitoring units have highlighted the importance of impaired respiratory control, suggesting that genetic variants involved in central respiratory drive represent strong candidates for determinants of SUDEP risk. Animal models have also implicated epilepsy genes, impaired cardiac electrophysiology and respiratory arrest in the pathogenesis of SUDEP. In particular, animal models have suggested KCN1A and SCN8A as SUDEP genes, and a mouse model of Dravet syndrome recapitulates features of the disease, including SUDEP. This review will highlight a mounting body of evidence for the involvement of genetic risk factors in SUDEP, with a particular focus on the role of cardiac arrhythmia genes in SUDEP.